Assessing anticoagulation in neonates with congenital diaphragmatic hernia during extracorporeal membrane oxygenation: does anti-factor Xa or thromboelastometry provide additional benefit? - Perez Ortiz, Alba; Dempfle, Carl-Erik; Jung, Toni; Doniga, Thalia; Weiß, Christel; Hetjens, Svetlana; Schaible, Thomas; Rafat, Neysan (Frontiers in Pediatrics, 2021)
Objective: The optimal management of anticoagulation in neonatal/pediatric patients during extracorporeal membrane oxygenation (ECMO) has not been established yet and varies greatly among ECMO centers worldwide. Therefore, we aimed to assess whether the use of anti-factor Xa assay and/or thromboelastometry correlate better than activated clotting time with heparin dose in newborns with congenital diaphragmatic hernia during ECMO. We also examined whether these coagulation assays correlate with thrombotic and/or hemorrhagic complications, when the management of anticoagulation is based only on activated clotting time values.Methods: A prospective observational study in a neonatal ECMO center was conducted. We included all neonates with congenital diaphragmatic hernia born in our institution between March 2018 and January 2019 and requiring support with venoarterial ECMO. A total of 26 ECMO runs were analyzed. During the study, the heparin dose was still adjusted according to activated clotting time values. Measurements of anti-factor Xa assay, activated partial thromboplastin time, and a thromboelastometry from the same blood specimen were performed twice a day.Results: Anti-factor Xa levels showed a moderate correlation with heparin dose, whereas the other tests showed a weak correlation. Four patients (17.4%) had thrombotic complications, 2 patients (8.7%) experienced life-threatening bleeding, and in 11 patients (47.8%) disseminated intravascular coagulation (DIC) occurred. Anti-factor Xa levels were lower in the group with thrombotic complications (0.23 vs. 0.27 IU/ml; p = 0.002), while activated partial thromboplastin time was higher in the group with hemorrhagic complications (69.4 s vs. 59.8 s; p = 0.01). In patients experiencing DIC, heparin dose and anti-factor Xa levels were lower, while no difference in activated clotting time and clotting time in INTEM and INTEM-HEPTEM were shown.Conclusions: Anti-factor Xa levels correlate better to heparin dose than activated clotting time. The use of anti-factor Xa assay instead of activated clotting time for dosing of unfractionated heparin could reduce thrombotic complications in neonates with congenital diaphragmatic hernia on ECMO support. The thromboelastometry showed no additional benefit for this purpose.
Gesehen am 26.10.2021